New record of the humpback whale (Megaptera novaeangliae) in the Adriatic Sea - Genov, Tilen; Kotnjek, Polona; Lipej, Lovrenc (Centro di ricerche scientifiche della Repubblica di Slovenia, 2015)
A report is submitted herein on the occurrence of a humpback whale in Slovenian territorial waters (Gulf of Trieste, North Adriatic Sea) during February, March and April 2009. This is a first confirmed and documented record of this species for Slovenia and the Gulf of Trieste.